Accurate Determination and Comprehensive Evaluation of Heavy Metals in Different Soils from Jilin Province in Northeast China. (29th April 2021) - Zhao, Yuyan; Zhang, Zeyu; Li, Bing; Zhao, Yu; Lu, Jilong; Tang, Xiaodan
Abstract: To provide technical support and theoretical guarantee for the prevention and control of soil heavy metal pollution, the main types of topsoil and parent material in Jilin Province were systematically collected, accurately tested by atomic fluorescence spectrometry and inductively coupled plasma mass spectrometry, and comprehensively evaluated through five indexes. By principal component analysis, it was initially judged that there were 2 or 3 major heavy metal sources in topsoil, which could be attributed to the parent material, soil-forming process, and/or anthropogenic factor. The pH of surface soil mainly depended on its parent material, and changed to a certain extent during its formation. The contents of heavy metals As, Hg, Cd, Cr, Cu, Ni, Pb, and Zn in surface soils were both significantly influenced by parent materials and soil-forming processes. Here the geo-accumulation index calculated by corresponding background value of parent material was more suitable for pollution assessment than the other four indexes, and the heavy metal contamination degree in each type of soil basically followed the order: Hg > Cd > Cu, Pb, Zn, As > Cr, Ni. Furthermore, the heavy metal contamination level in the types of soils was ranked as follows: cambisol, phaeozem > podzol, planosol > chernozem. The health risk assessment indicated that the soil in the study area had no significant carcinogenic or non-carcinogenic risks. Excluding the influence of parent material and soil-formation process, the comprehensive evaluation of soil heavy metal pollution will be more reasonable.